2018
DOI: 10.1111/tpj.13913
|View full text |Cite
|
Sign up to set email alerts
|

The PP2A‐interactor TIP41 modulates ABA responses in Arabidopsis thaliana

Abstract: Modulation of growth in response to environmental cues is a fundamental aspect of plant adaptation to abiotic stresses. TIP41 (TAP42 INTERACTING PROTEIN OF 41 kDa) is the Arabidopsis thaliana orthologue of proteins isolated in mammals and yeast that participate in the Target-of-Rapamycin (TOR) pathway, which modifies cell growth in response to nutrient status and environmental conditions. Here, we characterized the function of TIP41 in Arabidopsis. Expression analyses showed that TIP41 is constitutively expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 94 publications
3
33
1
Order By: Relevance
“…10 We have shown that mutants in TIP41, a predicted component of TOR signaling, are hypersensitive to ABA and NaCl, as well as to iron starvation conditions in root growth assays. 11 Thus, TIP41 is an integrator of responses to nutrient availability and abiotic stress, and a further link between TOR and ABA pathways.…”
mentioning
confidence: 99%
“…10 We have shown that mutants in TIP41, a predicted component of TOR signaling, are hypersensitive to ABA and NaCl, as well as to iron starvation conditions in root growth assays. 11 Thus, TIP41 is an integrator of responses to nutrient availability and abiotic stress, and a further link between TOR and ABA pathways.…”
mentioning
confidence: 99%
“…Using RNA transcriptome data from potato cells adapted to gradually increasing concentrations of polyethylene glycol (PEG) we identified Arabidopsis orthologous genes, and functionally analysed their role in responses to ABA and osmotic stress (Ambrosone et al, 2015, 2017; Punzo et al, 2018). Following the same rationale, we focused on a DNA-damage-repair/toleration protein coding gene (EST617924, GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%
“…Using RNA transcriptome data from potato (Solanum tuberosum) cells adapted to gradually increasing concentrations of polyethylene glycol (PEG) we identified Arabidopsis orthologous genes, and functionally analysed their role in responses to ABA and osmotic stress (Ambrosone et al, 2015(Ambrosone et al, , 2017Punzo et al, 2018). Following the same rationale, we focused on a DNA-damagerepair/toleration protein coding gene (EST617924, GenBank accession no.…”
Section: Drt111 Expression Is High In Seeds and Guard Cells And Is Inmentioning
confidence: 99%